A new species of Monilochaetes from Nothapodytes pittosporoides - Zhou, Si-Xuan; Qiao, Li-Jun; Kang, Ji-Chuan; Hyde, Kevin D.; Ma, Xiao-Ya (Phytotaxa, 2017)
Monilochaetes nothapodytis sp. nov. was isolated from healthy Nothapodytes pittosporoides in Tongren City, Guizhou Province, China. Molecular analysis based on combined ITS and LSU sequence data showed that M. nothapodytis formed a distinct clade with the type species M. infuscans and other species in this genus. Morphological examination showed that M. nothapodytis differs from other Monilochaetes species in its host and in having aseptate, ellipsoidal conidia, the micro-conidiophores are shorter and the micro-conidia are smaller than in other species. The new species is described and illustrated and an updated phylogenetic tree is presented for Glomerellales.